Development Of Unsaturated Polyester Hybrid Composites Filled With Empty Fruit Bunch And Oil Palm Ash - Mustahil, Noorul Linda Suraya (2017)
Oil Palm Empty Fruit Bunch (OPEFB) and Oil Palm Ash (OPA) were reported as among highly dumped oil palm waste. This research work aims to develop hybrid unsaturated polyester composites filled with OPEFB and OPA filler which emerges as a viable alternative to the existing polymer composites. Advantage of hybrid composite is one type of reinforcement/filler involved could complement with what are lacking in the other reinforcement/filler. In this study, OPEFB and OPA filler were mixed together into unsaturated polyester resin with different OPEFB to OPA filler ratio (0:100, 20:80, 40:60, 60:40, 80:20 and 100:0) and different filler sizes (60 mesh, 100 mesh and 200 mesh).